2021
DOI: 10.35808/ersj/2120
|View full text |Cite
|
Sign up to set email alerts
|

Development of Innovation Economy - Activity of Local Government in Poland

Abstract: Purpose:The paper aimed to check the activities of local governments contributing to the development of the innovation economy in Poland as well as to find the answer to the questions if local governments both support innovations, as well as implement innovations themselves. Moreover, the purpose of the paper was to find out if activities of local governments depend on their type (rural, urban, urban-rural) or not? Approach/Methodology/Design: In order to achieve that the method of desk research, quantitative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Although many references scientific categorize the affairs of innovation but the leads on the functioning of the economic, social, territorial, for example, what kind of support the government in SME food that improve the performance of innovation? [27] the relationship between entrepreneurship innovation, government regulation, and performance [28] Economic Development innovation [29] the innovation of government bonds in the growth of the capital market that appears [30] government subsidies on enterprise innovation: based on the perspective of the three-dimensional [31], Analysis Of the Role of the government In the Construction of the innovation System of the Region [32] How local government in social innovation to facilitate the community to thrive? [33] Then in the technical limitations for example the efficiency, performance, dimensions, context, characters, motivation as mentioned Whether the efficiency of government higher brings about innovation in higher?…”
Section: Resultsmentioning
confidence: 99%
“…Although many references scientific categorize the affairs of innovation but the leads on the functioning of the economic, social, territorial, for example, what kind of support the government in SME food that improve the performance of innovation? [27] the relationship between entrepreneurship innovation, government regulation, and performance [28] Economic Development innovation [29] the innovation of government bonds in the growth of the capital market that appears [30] government subsidies on enterprise innovation: based on the perspective of the three-dimensional [31], Analysis Of the Role of the government In the Construction of the innovation System of the Region [32] How local government in social innovation to facilitate the community to thrive? [33] Then in the technical limitations for example the efficiency, performance, dimensions, context, characters, motivation as mentioned Whether the efficiency of government higher brings about innovation in higher?…”
Section: Resultsmentioning
confidence: 99%
“…As a result of this narrow focus, innovation research has been unable to be fully integrated and its importance and impact assessed (Siguaw et al , 2006). There is also evidence to show that the government sector has a lower rate of innovation than the private sector (Derlukiewicz et al , 2021; Jalonen and Helo, 2020) and that there is a general lack of awareness about the importance of innovation in such a sector (Bloch and Bugge, 2013; Mulgan and Albury, 2003; Walker et al , 2002). The results of many studies on innovation are often confused and indecisive because there is no consensus on the role of innovation in the government sector, particularly on the long-term strategy of innovation and its orientation (Moussa et al , 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The results of many studies on innovation are often confused and indecisive because there is no consensus on the role of innovation in the government sector, particularly on the long-term strategy of innovation and its orientation (Moussa et al , 2018). A look at the literature shows that government studies have not paid enough attention to innovation orientation, which may be more important for an organisation’s long-term success (Derlukiewicz et al , 2021; Siguaw et al , 2006). Such an innovation orientation has not been formalised in the existing literature, even though there is a lot of research on innovation.…”
Section: Introductionmentioning
confidence: 99%
“…It cannot even be concluded that the known mechanisms of analysis and evaluation of the feasibility of investment projects can be universally applied to significantly different entities of public administration. A special dimension, when it comes to supporting innovation in the public sector, is the persistent socio-economic inequality between such entities, especially at the local level (Baranowski, 2017;Derlukiewicz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%